Effects of milk proteins on intracellular Ca2+ concentration and stallion sperm binding to zonae pellucidae - Coutinho da Silva, Marco Antonio, author; Carnevale, Elaine M., advisor; Squires, Edward L., committee member; Seidel, George, committee member; McCue, Patrick, committee member; Graham, James K., committee member (Colorado State University. Libraries, 2005)
The effects of semen extender components on the ability of stallion sperm to bind to the zona pellucida (ZP) and, the suitability of using bovine ZP for a ZP-binding assay for stallion sperm were investigated in a series of experiments. In Experiment I, similar numbers of stallion sperm bound to both bovine and equine ZP. In Experiment II, a three-fold increase in the number of sperm bound to ZP was observed when sperm were diluted in a skim-milk based diluent (EZM), compared to diluents which contained no milk (TALP, Lactose-EDTA, and EmCare®). In Experiment III, centrifuging the sperm through Percoll did not increase sperm binding to the ZP but did remove any positive effect of EZM on sperm-ZP binding. In Experiment IV, exposure of either sperm or ZP to EZM prior to co-incubation did not increase sperm binding to ZP, although the number of sperm bound to the ZP was higher if EZM was present during co-incubation. In Experiment V, sperm diluted in TALP containing skim-milk, EZM or INRA96® bound more efficiently to the ZP than sperm diluted in TALP without milk proteins. In Experiment VI, sodium caseinate (SC), native phosphocaseinate (NP) and caseinoglycopeptide were added to the sperm diluent, and increased sperm binding to the ZP in a dose-dependent manner. The objectives of subsequent experiments were to determine the effect of extracellular Ca2+ concentration and milk proteins (NP and SC) on intracellular Ca2+ concentrations of stallion sperm; and to determine the effects different caseins (α-, β-, κ-caseins) have on sperm binding to the ZP. Extracellular Ca2+ concentration (2 versus 4 mM) in the sperm diluents did not affect baseline intracellular Ca2+ concentration of sperm. However, incubating sperm in a medium containing 4 versus 2 mM Ca2+ resulted in higher (P<0.05) influx of Ca2+ into sperm after treatment with ionomycin. Addition of NP or SC to TALP did not affect the baseline intracellular Ca2+ or the influx of Ca2+ after ionomycin treatment. Sperm-ZP binding assays were performed by co-incubating stallion sperm and bovine ZP in TALP alone or TALP containing 1 or 3 mg/ml of individual caseins (α-, β-, κ-caseins). Co-incubating sperm and ZP in media containing single caseins resulted in similar numbers of sperm bound to the ZP compared to TALP. Higher (P<0.05) numbers of sperm were bound to ZP when co-incubation medium contained β-, κ-caseins, compared to α-casein. In conclusion, bovine ZP can be used for ZP-binding assays for stallion sperm. Co-incubating sperm and ZP in diluents containing milk or milk proteins markedly enhanced the number of sperm bound to the ZP. However, intracellular Ca2+ concentration of the sperm was not affected by milk proteins. It appears that β-, κ-caseins are responsible for enhancing sperm binding to the ZP, however the mechanism by which they enhance sperm binding is not known.
Keywords: anatomy and physiology; animals; veterinary services